The Happy Hopping of Transposons: The Origins of V(D)J Recombination in Adaptive Immunity - Shridharan, Rishi V.; Kalakuntla, Neha; Chirmule, Narendra; Tiwari, Bhavana (Frontiers in Ecology and Evolution, 2022)
Nearly 50% of the human genome is derived from transposable elements (TEs). Though dysregulated transposons are deleterious to humans and can lead to diseases, co-opted transposons play an important role in generating alternative or new DNA sequence combinations to perform novel cellular functions. The appearance of an adaptive immune system in jawed vertebrates, where the somatic rearrangement in T and B cells generates a repertoire of antibodies and receptors, is underpinned by Class II TEs. This review details the evolution of recombination activation genes (RAGs), components of adaptive immunity, from TEs, focusing on the structural and mechanistic similarities between RAG recombinases and DNA transposases. Studies reveal that as evolution occurred from a transposon precursor, DNA transposases developed a more targeted and regulated mechanism of action. Integral to regulation, we note key similarities and differences in the choice of DNA repair pathways following DNA transposition and RAG recombination. Understanding the regulation of V(D)J recombination from the perspective of DNA transposition may help future research in specifically targeting RAG proteins to rectify diseases associated with immune dysregulation.